(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
Interview with professor Dr. Maristela Abadia Fernandes Novaes, about her career as a fashion professional, teacher training and the importance of ressignification experiences in the process of creating clothes. The text addresses the relationship between moulage and modeling techniques, the creative process and the experiences of model makers and teachers in the area, as sensitive aspects of the teaching-learning of clothing modeling and its development, by going through decades of experiences, knowledge acquired and lived stories of professors as key factors to construction teaching.